ISLAMIC SCHOOL CULTURE POLICY IN THE QANUN LEVEL OF ACEH EDUCATION IMPLEMENTATION - Siraj Siraj; Basri Basri; Iis Marsithah; Asri Widiatsih; Efendi Efendi (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The implementation of islamic school cultural policies in accordance with Qanun Aceh Number 11 of 2014 is still not fully implemented optimally. The school residents have not been able to understand and translate the school culture according to Qanun and only describe according to their perspective; lack of socialization regarding the implementation of Qanun education in Aceh; and school culture is limited to the use of Islamic symbols in the school environment. The purpose of this study is to get an overview of the potential implementation of Islamic school cultural policies in accordance with the Qanun Aceh level. The research method uses qualitative with a case study design. The results showed that the embodiment of Islamic school culture can be seen from the value of excellence, namely the superior program of Tahfizh Al Qur'an and the teacher capacity building program. The value of responsibility by practicing the principles of Islamic teachings, cooperating in terms of kindness, commitment, integrity, tolerance, and realizing rights and obligations.